Hey guys, My math professor gave us a problem today that I have no clue how to solve. For a,b&c> 0, prove that a^(logb(c)) = c^(logb(a)). Where b is the base. Thanks for the help
Follow Math Help Forum on Facebook and Google+
Originally Posted by Reefer For a,b&c> 0, prove that a^(logb(c)) = c^(logb(a)). Where b is the base. Let $\displaystyle y=\left(\log_ba\right)\left(\log_bc\right)$. Then $\displaystyle y=\log_b\left(a^{\log_bc}\right)$ and also $\displaystyle y=\log_b\left(c^{\log_ba}\right)$.
View Tag Cloud